Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Perilaku Keuangan Pada Mahasiswa Universitas Sebelas Maret dengan Gender Sebagai Variabel Moderasi - Nurcayadi, Fatur Rochman; Indriayu, Mintasih; Hindrayani, Aniek (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aims to determine the effect of financial literacy on financial behavior with gender as a moderation variable. The sampling technique uses non-probability sampling techniques, namely purposive sampling with a sample of 364 UNS students consisting of the Faculty of Economics and Business (Development Economics, Accounting, Management) and the Faculty of Teacher Training and Education (Economic Education, Accounting, Office Administration). Test validity using product moment and reliability test using Cronbach's alpha. Data collection using questionnaires with Likert scale which is further converted to dummy variables and the data analysis used is binary logistic analysis. The results of this study obtained that: 1) Financial literacy has a positive and significant effect on financial behavior in UNS students; 2) Financial attitudes have a positive and significant effect on financial behavior in UNS students; 3) Male gender strengthens the relationship between the influence of financial literacy and financial attitudes on financial behavior in UNS students; 4) Women's gender strengthens the relationship between the influence of financial literacy and financial attitudes on financial behavior in UNS students